Methane Slip Abatement by Hydrogen Addition - Heikkilä, Sonja (My University, 2017)
The gas engines are a good alternative for peaking power, when the production of renewable energy is increasing. In the combustion of gas, unburned fuel, especially methane, tends to remain in the exhaust gas. The Pd-Pt/Al₂O₃ catalytic converters are proven to be the best for methane conversion but they are easily poisoned by sulphur and water from the exhaust. A poisoned catalyst is inactive and methane conversion is low. By regeneration it might be possible to revive the catalyst. According to the literature hydrogen injections are the most effective regeneration method. In the experiments, two temperatures and multiple H₂ injection concentrations (1 % to 2.5 %) and periods (10 minutes to 1 hour) were used for regeneration. The lower temperature of 380 °C was too low for the catalyst to activate. Experiments at 500 °C where more successful, but no long-lasting effect was achieved with the regenerations. In both experiments, sharp peaks of SO₂ were registered in the exhaust gas just after the start of the regeneration. It could be assumed that H₂ reacts in the catalyst and releases SO₂. Before this method is taken into everyday use, this topic needs to be studied further.
Keywords: natural gas engine; exhaust emissions; methane; catalyst; regeneration; fi=Energiatekniikka|en=Energy Technology|; fi=Energia- ja informaatiotekniikan ohjelma|